Brecht e a experiência do cinema : texto e montagem - Santos, Amanda Lemos Gonçalves dos (2018)
This work aims to analyze the work of the German Bertolt Brecht in the cinematographic field - in which he acted in several functions - considering the experiences of these works, through the film analysis in How worker lives(Germany, 1930), for portraying a peculiar period of his vast work. The arrival of Brecht to the cinema, here, in this present work, is configured as a synthesis of a trajectory that has as a prelude his poetic and theatrical work. The research seeks to analyze and critically reflect film works made by Brecht, from the expressive decade of the 20th through the troubled 1930s, under the perspectives of language, aesthetics and ideas tied to a revolutionary process. The experience and the aesthetic and political dimension of Brechtian thought are on the militant and vanguard cinema of the Weimar Republic and its roots in the Soviet Cinema, from where it recovered essential elements for the success of cinematographic productions, in the writing and in the stages of the montage. The theoretical formulations of the great thinker Walter Benjamin make an essential contribution to an accurate understanding of this important phase - Brecht's experience in cinema.